Chemical Structures and Pharmacological Properties of Typical Bioflavonoids in Polygonati Rhizoma (PGR). (20th September 2022) - Luo, Min; Hu, Zongren; Zhong, Zixuan; Liu, Lumei; Lin, Chengxiong; He, Qinghu
Abstract : Most medicines are coming with toxic and detrimental side effects. In addition, microbials are resisting the medicine. Therefore, alternative drugs with low toxic and side effects and low microbial resistance are needed. Plants offer good potential candidates due to a broad range of chemicals they contain. These chemicals have been studied, and research is still going on to probe chemical properties of plant chemicals. In China, traditional Chinese medicine is practised, whereby plant extracts are obtained, and then sold in packages for reasons like memory enhancement, cancer treatment, boosting immune system, and so on. Among the herbs cultivated in China is Polygonati rhizoma (PGR). This plant contains various bioflavonoids such as diosgenin, kaempferol, catechin, daidzein, and 3′ -methoxydaidzein. In this review, we discussed the pharmacological effects of these chemicals, including luteolin antimicrobial activity in a manner that it circumvents antibiotic resistance; rutin antivenom property; kaempferol as an agent that mitigates neuropathic pain; genistein anticancer property; isorhamnetin's ability to alleviate chronic obstructive pulmonary diseases (COPD); proanthocyanidins' ability to deal with diabetic neuropathy and analgesic property of catechin.